Silver-coated copper powder based on copper powder pretreatment and preparation method thereof

CN122687178APending Publication Date: 2026-09-04DK ELECTRONICS MATERIALS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610852135.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-12
Publication Date
2026-09-04

AI Technical Summary

Technical Problem

[0005]本发明针对现有银包铜粉的银壳成核不均匀,导致的银壳包覆不够均匀致密、表面不够光滑的问题,提供一种基于铜粉预处理的银包铜粉的制备方法,本发明通过可控的铜粉表面氧化处理,去除铜粉表面高活性位点,使银壳生长在成核阶段就做到在铜粉表面均匀分布,从而保证银壳的均匀致密性

Benefits of technology

1、本发明通过对铜粉表层进行预氧化,让存在“缺陷”的高活性位点,如棱角、边缘、凸起部位、晶格畸变形成的新鲜断裂面、表面羟基及不饱和价键等预先氧化为铜氧化物,在包覆银壳前再将铜粉表面的氧化物去除,使铜核表面活性趋于一致,这样镀银时铜核表面的银离子成核更加均匀,后续生长的银壳也更加均匀致密,有效解决了现有技术中银壳非均匀成核、局部银层过厚、出现银颗粒团聚及“岛状”包覆等问题,显著提升银包铜粉的包覆质量,为降低银含量、减小电阻率奠定基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application belongs to the technical field of conductive materials, and particularly relates to silver-coated copper powder based on copper powder pretreatment and a preparation method thereof. The preparation method is characterized in that the method comprises the following steps: (1) after the copper powder is laid flat, the copper powder is placed in a tube furnace, heated to a target temperature, air is introduced, heat preservation is performed, and cooling to room temperature is performed to complete the oxidation treatment of the copper powder; (2) a reducing agent, a complexing agent, a dispersing agent, a brightener and deionized water are stirred and mixed uniformly to prepare a reducing solution; then the copper powder after the oxidation treatment is added to the reducing solution, and continuous stirring is performed to obtain a copper powder-containing reducing solution; (3) silver nitrate solution is added to the copper powder-containing reducing solution, temperature is maintained, stirring is performed, and separation, washing and drying are performed to obtain the silver-coated copper powder based on the copper powder pretreatment. The silver-coated copper powder prepared by the application has good coating effect, so that the silver shell is uniformly distributed on the surface of the copper powder in the nucleation stage, thereby ensuring the uniform and dense coating of the silver shell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of conductive materials technology, specifically relating to a silver-coated copper powder based on copper powder pretreatment and its preparation method. Background Technology

[0002] Conductive pastes / inks using micron-sized silver powder as a conductive filler are widely used in conductive circuits, electrodes, and interconnect layers of various electronic components. However, the sharp increase in the price of precious metal raw materials has forced these industries to seek alternatives to silver using base metals. Copper has excellent electrical and thermal conductivity and its cost is much lower than silver, so it has been widely explored as a conductive functional material in electronics, new energy, and other fields. However, copper is chemically reactive and is easily oxidized in humid, high-temperature, or electric field environments, forming cuprous oxide or copper oxide layers with extremely poor conductivity, leading to a sharp decline in conductivity. In addition, copper ions have a strong tendency to migrate and easily diffuse along the insulating layer under electric field or humid and hot conditions, causing problems such as short circuits, leakage current, or shortened device lifespan. These defects severely limit the application of pure copper powder in long-life, high-reliability scenarios, such as solar cell electrodes, high-frequency electronic circuits, and electromagnetic shielding coatings.

[0003] Silver-coated copper powder has been proven to solve the problems of copper powder oxidation and copper ion migration, and it has been widely replacing silver powder in low-temperature conductive pastes. However, the resistivity of low-temperature conductive pastes prepared with silver-coated copper powder still lags behind that of pure silver paste. Driven by the industry's continuous pursuit of cost reduction and efficiency improvement, the future development direction of silver-coated copper powder is lower silver content and resistivity, and higher reliability. This places higher demands on the coating quality of the silver shell, requiring more uniform copper powder coating, higher silver shell density, and a smoother silver shell surface.

[0004] Copper powder is the core of silver-coated copper powder. The silver shell grows along the surface of the copper powder, and the surface structure of the copper powder has a great influence on the quality of the silver shell. The preparation methods of copper powder include physical methods and chemical methods. Both of these methods produce a lot of lattice distortion during the preparation of copper powder. In particular, particle collisions and breakage will form fresh fracture surfaces. These fracture surfaces have insufficient atomic coordination numbers and extremely high activity. The atomic coordination numbers of the edges, corners, and protrusions of copper powder particles are much lower than those of flat crystal faces (such as the (111) and (100) faces of cubic copper). The atoms are in an "unsaturated" state and have a stronger adsorption capacity for external ions. The difference in surface energy of different crystal faces will also lead to different activities. Generally, the reaction activity of high surface energy crystal faces (such as the (110) face) is significantly higher than that of low surface energy crystal faces. In addition, hydroxyl groups, unsaturated valence bonds, and residual functional groups on the surface of copper powder are also highly active sites. The highly active sites on the surface of copper powder are more likely to adsorb silver ammonia complex ions, which reduces the activation energy of the reduction reaction. In the early stage of chemical silver plating, non-uniform nucleation will be rapidly triggered, which manifests as excessively thick local silver layers, silver particle agglomeration, or even the formation of "island-like" coatings rather than continuous silver shells. Summary of the Invention

[0005] This invention addresses the problem of uneven nucleation of silver shells in existing silver-coated copper powders, which leads to insufficient uniformity and density of the silver shell coating and an uneven surface. It provides a method for preparing silver-coated copper powder based on copper powder pretreatment. This invention removes highly active sites on the surface of copper powder through controllable oxidation treatment, so that the silver shell is evenly distributed on the surface of copper powder during the nucleation stage, thereby ensuring the uniformity and density of the silver shell.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing silver-coated copper powder based on copper powder pretreatment includes the following steps: (1) Copper powder surface oxidation pretreatment: the particle size range is D 50 After spreading 1~10μm micron copper powder on the bottom of a quartz boat, it is placed in a tube furnace, heated to the target temperature, then air is introduced, kept at the temperature, and cooled to room temperature to complete the oxidation treatment of the copper powder. (2) Preparation of reducing solution and deoxidation of copper powder: Mix the reducing agent, complexing agent, dispersant, brightener and deionized water evenly to prepare a reducing solution; then add the oxidized copper powder to the reducing solution and stir continuously for 2-20 minutes to obtain a reducing solution containing copper powder. (3) Add silver nitrate solution to the copper powder-containing reducing solution, keep the temperature at 15-50℃, stir, separate, wash and dry to obtain silver-coated copper powder based on copper powder pretreatment.

[0007] Preferably, the heating rate in step (1) is 5-15℃ / min, the target temperature is 50-300℃, the air flow rate is 20-150mL / min, and the heat preservation time is 10-240min.

[0008] The reducing agent is glucose or ascorbic acid. The concentration of the reducing agent is 0.01-0.05 g / mL.

[0009] The complexing agent is one or more selected from ammonia, triethanolamine, ethylenediamine, disodium ethylenediaminetetraacetate, and triethylenetetraamine. Triethanolamine and disodium ethylenediaminetetraacetate are preferred complexing agents. The concentration of the complexing agent is 0.04-0.2 g / mL.

[0010] The concentration of the dispersant is 0.0001-0.01 g / mL.

[0011] The dispersants include polyethylene glycol, polyvinylpyrrolidone, and water-soluble dispersants.

[0012] The dispersant comprises polyethylene glycol, polyvinylpyrrolidone, and a water-soluble dispersant in a mass ratio of (2-3):(8-10):(5-6).

[0013] The method for preparing the dispersant includes the following steps: (1) Under a nitrogen protective atmosphere, polyetheramine and maleic anhydride were mixed and heated to react, yielding product 1; (2) Under a nitrogen protective atmosphere, product 1 is heated and a mixture containing styrene, allyl succinic anhydride and benzoyl peroxide is added dropwise. After the addition is complete, the mixture is kept at a constant temperature and the reaction is continued. n-Butanol and p-toluenesulfonic acid are added in sequence and the reaction is kept at a constant temperature. The pH is adjusted to obtain a water-soluble dispersant.

[0014] In the preparation of silver-coated copper powder, the dispersant has a significant impact on the suspension and dispersion of copper powder, the uniform reduction of silver ions, and the density of the silver shell. Currently, many types of dispersants are available on the market, such as polyethylene glycol, polyvinylpyrrolidone, and Tween. However, single or simple compound dispersants do not produce ideal results, mainly due to incomplete silver coating, pinholes or island defects, and poor bonding between the silver shell and the copper core. This invention improves the coating effect, reduces the defect density of the silver shell, and enhances density by compounding PEG, PVP, and a water-soluble dispersant in a specific mass ratio. The analysis shows that PEG, as a steric hindrance stabilizer, has flexible long chains that adsorb onto the surface of copper powder, providing a physical barrier to prevent particle aggregation. PVP, as a morphology control and protective agent, preferentially adsorbs onto specific crystal faces of silver, guiding the uniform reduction of silver ions while passivating the copper surface to inhibit oxidation. The water-soluble dispersant has a main chain composed of styrene-maleic anhydride copolymer and hydrophilic polyetheramine side chains. This dispersant is firmly anchored to the copper core surface through terminal amine or carboxylic acid groups. The long-chain polyetheramine side chains fully extend in water, providing a strong steric hindrance effect and interacting with PEG / PVP molecular chains through hydrogen bonds to form a multi-layered composite adsorption layer, thereby achieving complete coverage and stable dispersion of the copper powder surface. This invention first involves heating polyetheramine and maleic anhydride to perform an amidation reaction, followed by free radical copolymerization with styrene and allyl succinic anhydride. After the copolymerization reaction is completed, the remaining anhydride rings on the side chains of the copolymer are subjected to ring-opening esterification, and the pH of the system is adjusted to neutral to convert some of the carboxylic acid groups on the polymer chain into hydrophilic carboxylate salts, ensuring that the product is water-soluble.

[0015] The weight-average molecular weight of polyetheramine is 1700-2200.

[0016] The experiment revealed that the molecular weight of the polyetheramine and the type of succinic anhydride significantly affect the coating effect. When the weight-average molecular weight of the polyetheramine is controlled between 1700-2200, and maleic anhydride is used to prepare reactant 1, followed by the synthesis of a hydrophilic dispersant, and then compounded with PEG and PVP, the coating effect of silver-coated copper powder is significantly better than that of other molecular weights or the use of allyl succinic anhydride. The reason for this is that if the molecular weight of the polyetheramine is too low, the side chains are too short, resulting in insufficient steric hindrance, which cannot effectively prevent the copper powder from agglomerating. Furthermore, the anchoring layer of the dispersant on the copper surface is not thick enough, and silver ions are easily reduced rapidly in local areas to form a loose or dendritic silver layer. If the molecular weight is too high, the side chains are too long, which may over-coat the copper powder, hindering the silver ions from approaching the copper surface, resulting in a slow displacement reaction rate and discontinuous silver layer growth. Meanwhile, maleic anhydride hydrolyzes each anhydride group on the alternating copolymer backbone to generate a pair of adjacent carboxylate groups, endowing the polymer with excellent anionic properties and high charge density, enabling stable dispersion in aqueous media. In contrast, allyl succinic anhydride contains only one anhydride group per structural unit, resulting in a halved charge density after hydrolysis. Furthermore, the introduction of long-chain hydrophobic monomers further reduces the polymer's water solubility. As an electron-deficient monomer, maleic anhydride exhibits a strong tendency to copolymerize with electron-rich styrene, forming a more regular structure. This highly ordered structure allows for the uniform and precise distribution of polyetheramine side chains on the backbone, maximizing steric hindrance. Allyl succinic anhydride, due to its long side chains, has reduced polymerization activity and tends towards random copolymerization with styrene, resulting in uneven hydrophobic / hydrophilic regions. This directly affects the uniformity and stability of the final dispersant adsorption on the copper powder surface.

[0017] The brightener is N,N'-diphenylthiourea. The concentration of the brightener is 1-5 × 10⁻⁶. -6 mol / L.

[0018] The copper powder is micron-sized copper powder with a concentration of 0.04-0.1 g / mL.

[0019] The concentration of the silver nitrate solution is 0.15-0.5 g / mL. The stirring time is preferably 10-30 min.

[0020] The silver-coated copper powder prepared by the method is based on copper powder pretreatment.

[0021] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: 1. This invention pre-oxidizes the surface of copper powder, allowing highly active sites with "defects," such as sharp edges, protrusions, fresh fracture surfaces formed by lattice distortion, surface hydroxyl groups, and unsaturated valence bonds, to be pre-oxidized into copper oxides. These oxides are then removed from the surface of the copper powder before silver coating, making the surface activity of the copper nuclei more uniform. This results in more uniform nucleation of silver ions on the surface of the copper nuclei during silver plating, and a more uniform and dense silver shell subsequently grown. This effectively solves the problems of non-uniform nucleation of silver shells, excessively thick local silver layers, silver particle agglomeration, and "island-like" coating in existing technologies, significantly improving the coating quality of silver-coated copper powder and laying the foundation for reducing silver content and resistivity.

[0022] 2. This invention improves the coating effect, reduces the defect density of the silver shell, and improves the compactness by compounding PEG, PVP and water-soluble dispersant in a specific mass ratio.

[0023] 3. When the weight-average molecular weight of polyetheramine is controlled at 1700-2200, and maleic anhydride is used to prepare reactant 1, and then a hydrophilic dispersant is further synthesized, the coating effect of silver-coated copper powder is better after compounding with PEG and PVP. Detailed Implementation

[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] All raw materials used in the following embodiments of the present invention are commercially available products.

[0026] The PEG is PEG6000.

[0027] The PVP model is PVPK30.

[0028] Example 1 This embodiment provides a silver-coated copper powder based on copper powder pretreatment, the preparation method of which includes the following steps: 150g of micron-sized copper powder (D) 50The copper powder (6 μm thick) was spread evenly on the bottom of a quartz boat and placed in a tube furnace. The temperature was increased to 150°C at a rate of 10°C / min. Air was then introduced at a flow rate of 100 mL / min, and the mixture was kept at this temperature for 30 minutes. After cooling to room temperature, the copper powder oxidation process was completed. A reducing solution was prepared by mixing 100 g of triethanolamine, 30 g of disodium ethylenediaminetetraacetate, 12 g of dispersant, 1 mg of N,N'-diphenylthiourea, and 2 L of deionized water. The oxidized copper powder was then added to the reducing solution, and the mixture was stirred for 15 minutes. 100 mL of a 0.3 g / mL silver nitrate solution was then added to the reducing solution, and the temperature was maintained at 24°C. The mixture was stirred for 15 minutes to stop the reaction. The silver-coated copper powder was then separated, washed, and dried to obtain the finished silver-coated copper powder product.

[0029] The dispersant comprises PEG, PVP, and a water-soluble dispersant in a mass ratio of 2:10:5; the preparation method of the water-soluble dispersant includes the following steps: (1) Under a nitrogen protective atmosphere, polyetheramine and maleic anhydride were mixed in a molar ratio of 1.1:1, heated to 163°C, and kept at that temperature for 2.5 h to obtain product 1; polyetheramine: brand: Huntsman, model: JEFFAMINE ® M-2070; (2) Under a nitrogen protective atmosphere, product 1 is heated to 100°C; a mixture containing styrene, allyl succinic anhydride and benzoyl peroxide is added dropwise at a rate of 1 drop / s. After the addition is complete, the mixture is kept at 100°C for 1 hour. Then, n-butanol and p-toluenesulfonic acid are added sequentially and kept at 100°C for 7 hours. The mass ratio of product 1, styrene, allyl succinic anhydride, benzoyl peroxide, n-butanol and p-toluenesulfonic acid is 60:20:15:0.5:8.0:1. The pH is adjusted to neutral to obtain a water-soluble dispersant.

[0030] Example 2 The preparation method in this embodiment is the same as that in Example 1, except that the target oxidation temperature of copper powder is 150℃, the air flow rate is 50mL / min, and the holding time is 40min.

[0031] Example 3 The preparation method in this embodiment is the same as that in Example 1, except that the target temperature for copper powder oxidation is 200℃, the air flow rate is 20mL / min, and the holding time is 30min.

[0032] Example 4 The preparation method in this embodiment is the same as that in Example 1, except that the target temperature for copper powder oxidation is 250℃, the air flow rate is 50mL / min, and the holding time is 25min.

[0033] Example 5 The preparation method in this embodiment is the same as that in Example 1, except that the target temperature for copper powder oxidation is 200℃, the air flow rate is 70mL / min, and the holding time is 30min.

[0034] Example 6 The preparation method in this embodiment is the same as that in Example 1, except that the target temperature for copper powder oxidation is 150℃, the air flow rate is 100mL / min, and the holding time is 50min.

[0035] Example 7 The preparation method in this embodiment is the same as that in Example 1, except that the target temperature for copper powder oxidation is 180℃, the air flow rate is 100mL / min, and the holding time is 50min.

[0036] Comparative Example 1 The preparation method of this comparative example is the same as that of Example 1, except that the copper powder is not oxidized and is directly added to the reduction solution.

[0037] Comparative Example 2 The difference between this comparative example and Example 1 is that the dispersant is replaced with Tween85, the dispersant used in Example 1 of Chinese Patent CN118123016A, which describes a method for preparing uniformly coated silver-coated copper powder.

[0038] Comparative Example 3 The difference between this comparative example and Example 1 is that the dispersant includes PEG and PVP in a mass ratio of 1:5.

[0039] Comparative Example 4 The difference between this comparative example and Example 1 is that the dispersant includes PEG, PVP and Tween85 in a mass ratio of 2:10:5.

[0040] Comparative Example 5 The difference between this comparative example and Example 1 is that the dispersant includes polyethylene glycol, polyvinylpyrrolidone and a water-soluble dispersant in a mass ratio of 1:1:1.

[0041] Comparative Example 6 The difference between this comparative example and Example 1 is that the weight-average molecular weight of the polyetheramine is 1000, the brand is Huntsman, and the model is polyetheramine JEFFAMINE. ® M-1000.

[0042] Comparative Example 7 The difference between this comparative example and Example 1 is that maleic anhydride is replaced with an equimolar amount of allyl succinic anhydride.

[0043] Performance testing 1. Oxygen content analysis To test the coating quality of the silver shell, the silver-coated copper powder was heated in the air at 250°C for 90 minutes, and then the oxygen content of the powder was tested. The higher the oxygen content, the worse the quality of the silver shell, indicating that the coating of the copper core is defective or the silver shell is not dense enough.

[0044] The test results are shown in Table 1.

[0045] Table 1 Oxygen content test results As shown in Table 1, Examples 1-7 and Comparative Examples 1-7 all used the same copper powder, so the oxygen content of the original copper powder was the same. The oxygen content of the copper powder increased after surface oxidation pretreatment. The oxygen content of the silver-coated copper powder in Examples 1-7 after heating in air at 250°C was significantly lower than that in Comparative Example 1. This indicates that the highly active sites on the surface of the copper powder were removed after pre-oxidation, resulting in more uniform silver ion deposition during the silver plating process and achieving a higher quality silver shell. The oxygen content variation of the copper powder after surface oxidation pretreatment in Examples 1-7 followed the pattern that the higher the temperature, the greater the airflow, and the longer the holding time, the higher the oxygen content of the copper powder. The overall oxygen content of the copper powder after oxidation was controlled below 1%. Before silver plating, the oxides on the surface of the copper powder can be reduced by the amine-based alkaline complexing agent in the reduction solution. Therefore, the oxidation pretreatment does not affect the final electrical properties of the silver-coated copper powder, resulting in the oxygen content of the finally synthesized silver-coated copper powder being <0.1%, which is quite close.

[0046] 2. Slurry resistivity and viscosity The prepared silver-coated copper powder was mixed with nano-silver powder, organic additives, etc., to form a low-temperature silver-coated copper conductive paste. The resistivity of the paste was tested by printing the paste into electrode strips of 0.5 mm × 5 cm, heating them in air at 200°C for 7 minutes for thermal curing, and then using the four-probe method. The viscosity of the paste was measured using a viscometer, and viscosity data were recorded at three conditions: 10 rpm, 50 rpm, and 100 rpm.

[0047] Table 2 As shown in Table 2, the resistivity of the slurry of silver-coated copper powder in Examples 1-7 is better than that in Comparative Example 1, indicating that the silver shell of the examples is denser, has better conductivity, more uniform coating of the copper core, and better protection of the copper core; the viscosity of the examples is lower than that of the comparative example, indicating that the silver shell of the silver-coated copper powder in the examples is less prone to oil absorption and the surface of the silver shell is smoother; the tap density of the examples is greater than that of the comparative example, which further illustrates that the silver shell of the examples is denser.

[0048] The main advantage of this invention is that a more uniform and dense silver shell is prepared by pre-oxidation of the copper powder surface, which improves the conductivity of the silver-coated copper powder and reduces the viscosity of the slurry. As shown in Tables 1 and 2, the silver-coated copper powder of the embodiments of this patent has a more uniform and dense silver shell. After heat treatment at 250°C for 90 minutes in air, the oxygen content is significantly lower than that of the comparative example. This indicates that the silver-coated copper powder of the embodiments has better oxidation resistance and reliability. The resistivity of the low-temperature slurry prepared using the silver-coated copper powder of the embodiments is significantly better than that of the comparative example. This indicates that the silver shell of the silver-coated copper powder of the embodiments, which removes active sites by surface pre-oxidation of the copper powder, is more dense and has better conductivity. The slurry viscosity of the silver-coated copper powder of the embodiments is also lower than that of the comparative example. This indicates that the surface of the silver-coated copper powder of the embodiments is smoother and the silver shell is denser. The lower slurry viscosity is also more conducive to the practical application of the slurry, such as better ink return and faster printing speed. In addition, the greater tap density of the embodiments also demonstrates the uniformity and density of the silver shell of the embodiments.

[0049] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing silver-coated copper powder based on copper powder pretreatment, characterized in that, Includes the following steps: (1) Copper powder surface oxidation pretreatment: After spreading the copper powder evenly, put it into a tube furnace, heat it to the target temperature, then introduce air, keep it warm, and cool it to room temperature to obtain copper powder after oxidation treatment; (2) Preparation of reducing solution and deoxidation of copper powder: The reducing agent, complexing agent, dispersant, brightener and deionized water are stirred and mixed evenly to prepare a reducing solution; then the oxidized copper powder is added to the reducing solution and stirred continuously to obtain a reducing solution containing copper powder. (3) Add silver nitrate solution to the copper powder-containing reducing solution, stir, separate, wash and dry to obtain silver-coated copper powder based on copper powder pretreatment.

2. The method for preparing silver-coated copper powder based on copper powder pretreatment according to claim 1, characterized in that, The dispersants include polyethylene glycol, polyvinylpyrrolidone, and water-soluble dispersants.

3. The method for preparing silver-coated copper powder based on copper powder pretreatment according to claim 2, characterized in that, The dispersant comprises polyethylene glycol, polyvinylpyrrolidone, and a water-soluble dispersant in a mass ratio of (2-3):(8-10):(5-6).

4. The method for preparing silver-coated copper powder based on copper powder pretreatment according to claim 3, characterized in that, The method for preparing the dispersant includes the following steps: (1) Under a nitrogen protective atmosphere, polyetheramine and maleic anhydride were mixed and heated to react, yielding product 1; (2) Under a nitrogen protective atmosphere, product 1 is heated and a mixture containing styrene, allyl succinic anhydride and benzoyl peroxide is added dropwise. After the addition is complete, the mixture is kept at a constant temperature and the reaction is continued. n-Butanol and p-toluenesulfonic acid are added in sequence and the reaction is kept at a constant temperature. The pH is adjusted to obtain a water-soluble dispersant.

5. The method for preparing silver-coated copper powder based on copper powder pretreatment according to claim 4, characterized in that, The weight-average molecular weight of polyetheramine is 1700-2200.

6. The method for preparing silver-coated copper powder based on copper powder pretreatment according to claim 1, characterized in that, The reducing agent is glucose or ascorbic acid.

7. The method for preparing silver-coated copper powder based on copper powder pretreatment according to claim 1, characterized in that, The heating rate in step (1) is 5-15℃ / min, the target temperature is 50-300℃, the air flow rate is 20-150mL / min, and the holding time is 10-240min.

8. The method for preparing silver-coated copper powder based on copper powder pretreatment according to claim 1, characterized in that, The complexing agent is one or more of ammonia, triethanolamine, ethylenediamine, disodium ethylenediaminetetraacetate, and triethylenetetramine.

9. The method for preparing silver-coated copper powder based on copper powder pretreatment according to claim 1, characterized in that, The copper powder mentioned is micron-sized copper powder with a particle size range of D. 50 The range is 1~10μm.

10. A silver-coated copper powder based on copper powder pretreatment, prepared by the method of any one of claims 1-9.

Citation Information

Patent Citations

  • Preparation method of uniformly-coated silver-coated copper powder and silver-coated copper powder

    CN118123016A